2006
DOI: 10.1111/j.1398-9995.2005.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in every fifth child in Oslo, Norway: a 10‐year follow up of a birth cohort study*

Abstract: Childhood asthma apparently continues to increase in Oslo, having affected every fifth 10-year-old child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(58 citation statements)
references
References 31 publications
2
53
2
1
Order By: Relevance
“…The prevalence of asthma found in the present study is lower than the prevalence reported in other European countries as Norway, where the prevalence was 11.1% in 10 year-old children (Lødrup Carlsen et al, 2006), Portugal, where the prevalence was 12.9% in 13-year-old children (Falcão et al, 2008), Greece, where the prevalence was 9.0% and 5.0% at 7 and 18 years, respectively (Bacopoulou et al, 2009), or France, where the prevalence among children between 11 and 14 years was 9% (Delmas et al, 2009). Nevertheless, our results are more proximal to the prevalence found in Sweden children (5.9%) from 5-14 years old (Kim et al, 2005), Dutch children (6.5%), who had the same range age than children studied in our study (8-13 years) (Tabak et al, 2006) or One-way ANOVA was used to identify significant differences between children with and without asthma.…”
Section: Discussioncontrasting
confidence: 55%
“…The prevalence of asthma found in the present study is lower than the prevalence reported in other European countries as Norway, where the prevalence was 11.1% in 10 year-old children (Lødrup Carlsen et al, 2006), Portugal, where the prevalence was 12.9% in 13-year-old children (Falcão et al, 2008), Greece, where the prevalence was 9.0% and 5.0% at 7 and 18 years, respectively (Bacopoulou et al, 2009), or France, where the prevalence among children between 11 and 14 years was 9% (Delmas et al, 2009). Nevertheless, our results are more proximal to the prevalence found in Sweden children (5.9%) from 5-14 years old (Kim et al, 2005), Dutch children (6.5%), who had the same range age than children studied in our study (8-13 years) (Tabak et al, 2006) or One-way ANOVA was used to identify significant differences between children with and without asthma.…”
Section: Discussioncontrasting
confidence: 55%
“…T1D patients were diagnosed according to EURODIAB criteria. 39 Allergic asthma was diagnosed based on having two of the three following criteria in the presence of at least one positive skin prick test against a standard panel of food and inhalant allergens: 38,40 (1) symptoms, (2) medication, (3) a doctor's diagnosis by the age of 10.…”
Section: Methodsmentioning
confidence: 99%
“…Both the asthma cases and the T1D controls and asthma controls were selected from a general Norwegian population-based birth cohort study, the ECA. 38 The control groups used in the T1D and asthma analyses are not totally identical, as the T1D control group included children without a diagnosis of T1D, whereas the asthma control group included children without a diagnosis of allergy or asthma. More than 95% of the cases and controls were of Norwegian ethnicity.…”
Section: Subjectsmentioning
confidence: 99%
“…Det er angitt at mellom 1 500 og 3 000 barn pr. år fødes med en eller flere misdannelser (Parelius & Aag, 2008 Norske studier angir at 20-25 % av norske barn har eller har hatt astma ved 10 års alder (Carlsen et al, 2006), men det er et stort spenn i alvorlighet av sykdommen. Man finner ingen geografiske forskjeller i forekomst av astma (Nystad et al, 1997 …”
Section: Faglig Samarbeidunclassified